Electrocatalytic Behavior of PtCu Clusters Produced by Nanoparticle Beam Deposition - Spadaro, Maria Chiara; Humphrey, Jo J. L; Cai, Rongsheng; Martínez, Lidia; Haigh, Sarah J; Huttel, Yves; Spencer, Steve J; Wain, Andrew J; Palmer, Richard (Journal of physical chemistry. C, 2020)
State-of-the-art electrocatalysts for electrolyzer and fuel cell applications currently rely on platinum group metals, which are costly and subject to supply risks. In recent years, a vast collection of research has explored the possibility of reducing the Pt content in such catalysts by alloying with earth-abundant and cheap metals, enabling co-optimization of cost and activity. Here, using nanoparticle beam deposition, we explore the electrocatalytic performance of PtCu alloy clusters in the hydrogen evolution reaction (HER). Elemental compositions of the produced bimetallic clusters were shown by X-ray photoelectron spectroscopy (XPS) to range from 2 at. % to 38 at. % Pt, while high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) combined with energy dispersive X-ray (EDX) spectroscopy indicated that the predominant cluster morphologies could be characterized as either a fully mixed alloy or as a mixed core with a Cu-rich shell. In contrast with previous studies, a monotonic decrease in HER activity with increasing Cu content was observed over the composition range studied, with the current density measured at -0.3 V (vs reversible hydrogen electrode) scaling approximately linearly with Pt at. %. This trend opens up the possibility that PtCu could be used as a reference system for comparing the composition-dependent activity of other bimetallic catalysts.